(untitled) (The Review of Diabetic Studies, 2024)
Background: n light of the severe effects of floods, fires, storms, and terrorist attacks, our planet is about to enter its most perilous phase in recent decades. Furthermore, important occurrences overwhelm daily existence. The frequency of large-scale catastrophic events that result in significant property losses, human casualties, and a variety of other effects that are impossible to handle on one’s own has dramatically increased in recent years. Giving healthcare professionals the resources they need to improve their odds of surviving and reduce their losses is known as disaster preparedness. Aim of the study: The study aims to assess family medicine physician knowledge of their roles in disaster health management about emergency preparedness and compare the level of nurses’ knowledge about emergency preparedness between governmental and private hospitals. Setting of the study: This study was conducted in family practice clinics in priamarey care organization (N=30) in Saudi Arabia Study subjects Convenient sampling includes family medicine physician who were working in the previously mentioned setting with experience more than 6 month and were available during time of data collection and distributed (n=230). Results: the current study revealed that poor family medicine physician ’ knowledge about their role in emergency preparedness with mean percent score (49.20 ± 11.11). The mean percentage of general knowledge about emergency preparedness was (56.12 ± 18.84) while the specific knowledge about emergency preparedness was (47.07 ± 12.76). Conclusion: the present study concluded that the family medicine physician ’ knowledge of their role about emergency preparedness is poor in both hospitals and nurses less prepared to deal with different victims of different type of large-scale emergency events. Recommendation: Develop crisis training workshop proposal to Ministry of Health and Population for nurses before employment in healthcare settings.